Konversi Agama di Kalangan Etnis Tionghoa: Motivasi, Adaptasi dan Konsekuensi - Rakhmat Hidayat; Dessita Putri Sherina (Hayula: Indonesian Journal of Multidisciplinary Islamic Studies, 2020)
This paper aims to describe ​​the process of religious conversion conducted by five ethnic Chinese muallafs at Yayasan Haji Karim Oei Jakarta. This study also describes the state of anomie experienced by muallafs in the post-religious conversion time and the adaptation to face the anomic circumstances. Qualitative approach with case study method is the research approach used in this research. Observations and interviews were used as data collection. This study uses the concept of systemic stage model by Rambo Lewis to examine the process of religious conversion and the concept of anomie by Emile Durkheim to examine the social state of post-religious conversion. In fact, that the religious conversion is caused by internal factor which is inner crisis and also caused by external factors such as living in a social sphere dominated by the majority of Muslims, the factor of marriage, and religious lectures performed by the religious leaders.